Diabetic Foot - Rehman, Faiz ur; Nadir, Shahnaz; Noor, Seema (Journal of Postgraduate Medical Institute, 2011)
to evaluate the precipitating causes, severity, and complications of diabetic foot. This study carried out a study in Medical C unit of KTH, Peshawar. It was a longitudinal study done from June 2000 to December 2001. A total of 68 patients were studied having diabetic foot. Swabs for culture and sensitivity wer taken. Other complications of diabetes were recorded. Based on the observed commonest organism involved, appropriate antibiotic therapy was started promptly, besides doing surgical management of the wound. Diabetic foot is still common and requires proper management and counselling of the patients.